Innovation practices and Malay restaurant business growth performance / Raja Puteri Saadiah Raja Abdullah, Siti Suriawati Isa and Hashim Fadzil Arifin - Raja Abdullah, Raja Puteri Saadiah; Isa, Siti Suriawati; Arifin, Hashim Fadzil (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2023)
The restaurant sector is experiencing a fast and unpredictable evolution, resulting in varying levels of economic expansion. Undeniably, it is one of the most rapidly expanding sub-sectors within the hospitality and tourism industries. The rapid advancement of new technology is responsible for this expansion since it improves customer service and expands the selection of products. Malaysia is a diverse country with a multicultural and multi-ethnic population consisting of several ethnic groups, including Malays, Chinese, Indians, and others. Despite the fact that Malay is the biggest ethnic group in Malaysia, it is improbable that this particular ethnic restaurant would prosper in its economic endeavours. This implies that Malay restaurants have shortcomings in several areas, which limits the industry's ability to expand and thrive. The aim of this study is to investigate the correlation and viewpoints of Malay restaurant managers and owners on innovation practices and their influence on company growth performance, eventually resulting in enhanced customer service and heightened profitability. The findings from the surveys, in which 440 restaurant managers and owners participated, indicate that the implementation of innovative methods has a significant influence on the business's growing performance.